Vitamin D deficiency and duration of COVID-19 symptoms in UK healthcare workers - Chadda, Karan R.; Roberts, Sophie A.; Lugg, Sebastian T.; Faniyi, Aduragbemi A.; Faustini, Sian E.; Webster, Craig; Duffy, Joanne E.; Hewison, Martin; Shields, Adrian; Richter, Alex G.; Parekh, Dhruv; Scott, Aaron; et al. (Frontiers in Medicine, 2024)
Objectives Vitamin D has a role in the innate immunity against pathogens and is also involved in mechanisms for reducing inflammation. VD deficiency (VDD) may increase COVID-19 infection susceptibility, however research is limited on the association between VDD and COVID-19 symptom prevalence and duration. The study aimed to determine whether VDD is a risk factor for the presence and extended duration of COVID-19 symptoms. Methods Data was analyzed from NHS healthcare workers who isolated due to COVID-19 symptoms as a part of the COVID-19 convalescent immunity study between 12th to 22nd May 2020. Participants self-reported the presence and duration of viral symptoms. Anti-SARS-CoV-2 antibodies and vitamin D (25(OH)D3) serum levels were measured on day of recruitment. VDD was defined as 25(OH)D3 levels of < 30 nmol/l. Results Of the 392 participants, 15.6% (n = 61) had VDD. VDD participants had more symptoms overall (p = 0.0030), including body aches (p = 0.0453), and extended duration of body aches (p = 0.0075) and fatigue (p = 0.0127). Binary logistic regression found that both VDD (OR 3.069, 95% CI 1.538–6.124; p = 0.001) and age (OR 1.026, 95% CI 1.003–1.049; p = 0.025) were independently associated with extended durations of body aches. VDD (OR 2.089, 95% CI 1.087–4.011; p = 0.027), age (OR 1.036, 95% CI 1.016–1.057; p < 0.001) and seroconversion (OR 1.917, 95% CI 1.203–3.056; p = 0.006), were independently associated with extended durations of fatigue. Conclusion VDD is a significant independent risk factor for extended durations of body aches and fatigue in healthcare workers who isolated for COVID-19 viral symptoms. Vitamin D supplementation may reduce symptom duration and is thus an area for future research.